EVALUATION OF ANTIEPILEPTIC ACTIVITY OF ETHANOLIC EXTRACT OF AZIMA TETRACANTHA ROOT IN MICE - Eerike, Madhavi; Konda, Venu Gopala Rao; Arunachalam, Ruckmani; Dawood, Umar (International Journal of Current Pharmaceutical Research, 2016)
Objective: To evaluate the antiepileptic activity of ethanolic extract of Azima tetracantha root (EEATR) against Maximal electroshock (MES) and Pentylene tetrazole (PTZ) induced seizures in mice. Methods: 48 adult male mice were used and 4 groups with six in each were allocated to each model. 4 Groups are divided into control, standard and two test groups. Control group received normal saline, standard group, Sodium valproate-200 mg/kg and the two test groups received ethanolic extract of roots of Azima tetracantha (EEATR) 250 and 500 mg/kg respectively. Antiepileptic activity was assessed based on hind limb tonic extension duration, onset of convulsions and mortality. The results were compared with control and standard. Results: In MES model EEATR reduced the duration of hind limb extension (HLE) and seizure protection was 50% and 66.6% with 250 and 500 mg/kg respectively. In PTZ model both the doses of EEATR delayed the onset of clonic phase and prevented death in 50% of animals in group treated with 500 mg/kg EEATR, similar to sodium valproate. Results were analyzed by ANOVA with p<0.05 considered as significant. Conclusion: EEATR has shown anticonvulsant activity in both MES and PTZ models. 500 mg/kg of EEATR has better protection than 250 mg/kg against seizure in MES model and equally efficacious as sodium valproate standard in PTZ model.